Chronic wound mitomycin-c-induced animal models - Andreas Ariawan; Aditya Wicaksana; Aditya Rifqi Fauzi; Rosadi Seswandhana* (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
ABSTRACTChronic wound is a problem often encountered, especially in areas that do not have adequate health facilities. Some of the factors that caused the injury are mechanical, chemical, electrical, or heat. Chronic inflammation and bacterial infections are the two major factors that affect the process of wound chronicity. Mitomycin-C (MMC) is widely used as an intravenous, oral, and topical anti-cancer drug. MMC that is applied topically to a wound can cause cross-linking and decrease or stop the process of DNA transcription so that the wound will not develop the healing phase because MMC works as an inhibitor of fibroblast and proliferation that can inhibit wound healing. This study aimed to create animal models of chronic wound using topical MMC compared to those who given exposure of NaCl without topical MMC. This study used eight female Wistar rats aged 70 to 90 days, weighed between 300 to 350 grams. Wounds were made in the hip area with a diameter of approximately two centimeters. The subjects were divided into two groups. The first group, we compressed the wounds using sterile gauze moistened with MMC 0.5 mg/ml for 5 minutes and rinsed with a saline solution as much as 10 ml6. The second group was compressed using sterile gauze moistened with saline for 5 minutes. On day 3, 5, and 15 we observed the wound profile that was consist of diameter (as an indicator of wound healing), necrosis, and the consistency. The wounds that were compressed using MMC showed brownish-black, dry, thick chronic wounds and took longer to heal compared to those with NaCl. Application of MMC topically on the wound after day 15 showed an inhibition of wound healing process. The animal models showed a slower decrease of wound diameter, fewer scar tissue formation, and development of necrotic tissue.